Development of Small Business and Private Entrepreneurial Activity Through Vocational Direction - Ibragimova, M.; G'ulomovna, Ibragimova Maryamkhan (Journal of Research in Innovative Teaching and Inclusive Learning, 2023)
This article describes innovative activity in educational institutions and its impact on the quality of education.